DMEK outcome after one year – Results from a large multicenter study in Germany. Issue 2 (30th September 2022) - Spaniol, Kristina; Hellmich, Martin; Borgardts, Klara; Girbardt, Christian; Maier, Philip; Reinhard, Thomas; Torun, Necip; Maier, Anna‐Karina; Thaler, Sebastian; Bartz‐Schmidt, Karl U.; Wiedemann, Peter; Seitz, Berthold; et al.
Abstract: Purpose: Descemet membrane endothelial keratoplasty (DMEK) accounts for >50% of all corneal transplants in Germany. So far, no data from such a large multicenter study have been published. Methods: This retrospective study included 3200 DMEKs at seven departments performed for Fuchs endothelial corneal dystrophy (FECD) or bullous keratopathy (BK). We evaluated best corrected visual acuity (BCVA, logMAR), endothelial cell density (ECD, cells/mm 2 ), minimal corneal thickness (CT, μm), rebubbling‐, primary transplant failure‐ and immune reaction‐rate. Changes over time were evaluated by linear mixed models for repeated measures and correlation with case number by center by weighted linear regression. Results: For patients without vision‐limiting comorbidities (74% of all analysed eyes, n = 2270), mean BCVA improved from 0.6 ± 0.4 logMAR to 0.2 ± 0.2 logMAR 6 months ( p < 0.001, n = 1441) and 0.1 ± 0.2 logMAR 12 months ( p = 0.001, n = 1402) postoperatively. BK‐ had a worse BCVA compared to FECD‐patients (0.3 ± 0.5 vs. 0.1 ± 0.2 logMAR [ p < 0.001] at 1 year). ECD declined from 2465 ± 259 cells/mm 2 ( n = 2876 preoperatively) to 1587 ± 433 cells/mm 2 after 12 months ( p < 0.001, n = 1237). Mean rebubbling rate was 0.4 ± 0.7/eye. 784 eyes (25%) received at least one rebubbling. More rebubblings correlated with a lower ECD, a worse BCVA, a higher CT, and higher transplant failure and rejection rates ( p < 0.001, p = 0.013 for BCVA at 12 months). A single rebubbling did not influence the BCVA ( p = 0.785). Graft failure rate was 3% ( n = 67), rejection rate 1.5% ( n = 48). Conclusion: Descemet membrane endothelial keratoplasty increases visual acuity with low transplant failure‐ and rejection‐rates. FECD has a better outcome than BK. Since a quarter of all patients need a rebubbling, this should be included in the informed consent. Remarkably, one rebubbling has no influence on the outcome.